2021
DOI: 10.1177/1368430221998781
|View full text |Cite
|
Sign up to set email alerts
|

(Un)masking threat: Racial minorities experience race-based social identity threat wearing face masks during COVID-19

Abstract: During the COVID-19 pandemic, racial minorities in the United States were left in a double bind when deciding to wear face masks to prevent the spread of the virus: risk being racially profiled or risk COVID-19. Two studies examine Black and Asian individuals’ experiences of race-related social identity threat wearing face masks during COVID-19, and its impact on safety and health behaviors. Black, Asian, and White participants in the United States responded to surveys (S1: N = 776; S2: N = 534) on their exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…The findings of the present study demonstrated that ethnic discrimination was uniquely associated with COVID-19 fears. To date, much of the research on the effects of COVID-19 among college students of color has focused on the adverse effects of pandemic-related discrimination toward Asian American college students, for their presumed role in spreading the infection (Haft & Zhou, 2021; Liu et al, 2020), and African American college students for compliance with mask mandates (Kahn & Money, 2021; Lund, 2021). Findings from the present study expand on this literature to show that Latinx college students have also experienced discrimination during the pandemic in the form of devaluation of intelligence and verbal rejection (e.g., hearing stereotypical and offensive comments about one’s ethnic group).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study demonstrated that ethnic discrimination was uniquely associated with COVID-19 fears. To date, much of the research on the effects of COVID-19 among college students of color has focused on the adverse effects of pandemic-related discrimination toward Asian American college students, for their presumed role in spreading the infection (Haft & Zhou, 2021; Liu et al, 2020), and African American college students for compliance with mask mandates (Kahn & Money, 2021; Lund, 2021). Findings from the present study expand on this literature to show that Latinx college students have also experienced discrimination during the pandemic in the form of devaluation of intelligence and verbal rejection (e.g., hearing stereotypical and offensive comments about one’s ethnic group).…”
Section: Discussionmentioning
confidence: 99%
“…There was also some evidence of similar processes of categorisation as behaviour around mask wearing intersected with other markers of inclusion and exclusion, such as ethnicity. In the American context, Kahn and Money ( 2021 ) find that people from minoritized backgrounds experience mask‐related, race‐based social identity threat—that is, the fear that they will be treated differently or devalued because of their ethnicity when wearing a mask. While we did not find clear evidence of such perceptions among our participants, increases in xenophobia, in the form of physical and verbal abuse, have also been experienced by people of East Asian origin in countries across the world (Ng, 2020 ), including the UK.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the midst of the pandemic have already shown that individuals have diminished social cohesion and identification with broader categories feeding polarization and extremism, such as an increase in rejection toward the outgroup, greater prejudice, discrimination, stigma, race-based threat, and xenophobia (Roberto et al, 2020;see Gover et al, 2020;Inman et al, 2021;Li and Nicholson, 2021;Gao, 2022;Kahn and Money, 2022). In this regard, the broadest, and at the same time the most inclusive, superordinate level of identification which is IWAH can help individuals, at least to some extent, reduce intergroup threats (Riek et al, 2010).…”
Section: Discussionmentioning
confidence: 99%